Automating the group-theoretic-based construction procedure for the (nxn)/k semi-Latin square - Chigbu P.E.; Eze B.C. (Utilitas Mathematica, 2001)
We give and discuss a program in Qbasic language that enables one generate and construct the (nxn)/k semi-Latin squares which were originally generated and constructed via the systematic group-theoretic algorithm of Bailey and Chigbu [2].